Pengembangan Model ACPAE (Activity, Cooperative Learning, Project, Action, Exercise) dalam Pembelajaran Matematika Di SMP - Budianti, Fitria; Purnomo, Sujoko; Rahayuningsih, Sri (FKIP Universitas Wisnuwardhana, 2021)
This study aims to develop a valid, practical, and effective ACPAE learning model that can restore students’ self-efficacy. The development of the ACPAE model is a modification of PACE learning by adding one stage in the form of action. Less varied learning models result in students being bored when learning mathematics is taking place. For mathematics learning to run more actively and achieve learning objectives, the learning model to be applied must be appropriate. Students perceive mathematics as a difficult and tiring subject. This results in decreased students’ self-efficacy. The data analysis technique was obtained from the validity test questionnaire, practicality test, and effectiveness test results with 15 junior high school students as the subject. The results showed that the ACPAE model of learning could increase students' activeness in learning. The level of self-efficacy of students was shown by daring to interact in group discussions and appearing confident in front of the class. Based on the results of the validity test, the ACPAE learning model module obtained a value of 78.8%, for Lesson Plan obtained a value of 76.6%, for Student Worksheet obtained a value of 76.3%, for student response questionnaires received a value of 88.3% while for the percentage of learning completeness by 86.6%. So that when viewed from the assessment criteria, the ACPAE model is very appropriate to be used as a variation of the mathematics learning model.